Definition of phraseological units, their semantic features, history of the study of phraseological units - Rustamova Nazokat Abdullayevna (International Journal on Orange Technologies, 2021)
This article informs us about one of the linguistics branch which study the main source of language such as word combinations, linguistic units, phraseological expressions. Also in this paper, we can look back to the history of phraseology, the achievements of science and future practice on this issue. The ideas in the article are not only written or informed but also proven by concrete facts and examples.